2012
DOI: 10.1074/jbc.m112.343079
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Bound to the First IQ Motif Is Responsible for Calcium-dependent Regulation of Myosin 5a

Abstract: Background: Myosin 5a ATPase activity is regulated by calcium. Results: The ATPase of the truncated myosin 5a having the motor domain and the first IQ motif is inhibited by its tail in a calcium-dependent manner. Conclusion:The calmodulin in the first IQ motif of myosin 5a is responsible for calcium-dependent regulation. Significance: This presents a new paradigm for calcium regulation of unconventional myosins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 37 publications
2
41
0
1
Order By: Relevance
“…We showed previously that Myo5a-GTD inhibits not only the ATPase activity of Myo5a-HMM but also that of Myo5a-S1 containing the motor domain and the IQ1 motif (34). Similarly, we found that Myo5c-GTD inhibits the ATPase activity of Myo5c-S1 in a Ca 2ϩ -dependent manner (Fig.…”
Section: The Atpase Activity Of Myo5c Is Inhibited By Its Gtd In a Casupporting
confidence: 73%
See 2 more Smart Citations
“…We showed previously that Myo5a-GTD inhibits not only the ATPase activity of Myo5a-HMM but also that of Myo5a-S1 containing the motor domain and the IQ1 motif (34). Similarly, we found that Myo5c-GTD inhibits the ATPase activity of Myo5c-S1 in a Ca 2ϩ -dependent manner (Fig.…”
Section: The Atpase Activity Of Myo5c Is Inhibited By Its Gtd In a Casupporting
confidence: 73%
“…Thus, CaM, particularly the C-lobe, should have a different conformation when bound to the IQ1 of Myo5a or to the IQ1 of Myo5c. Previously, our biochemical analyses have shown that the C-lobe of CaM bound to IQ1 of Myo5a is critical for the interaction with the GTD (34). We therefore proposed that the H11-H12 loop of the GTD interacts with the C-lobe of CaM bound to the IQ1 motif (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Oligonucleotides were synthesized by Invitrogen. Actin, CaM, and MLCK (myosin light chain kinase) were prepared as described previously (22,23). Two mouse myosin-5a constructs, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Two mouse myosin-5a constructs, i.e. Myo5a-1IQ (containing the motor domain and 1st IQ, amino acids 1-791) and Myo5a-⌬T (myosin-5a with the globular tail domain deleted), were prepared as described (23,24). SkM (skeletal muscle myosin) was prepared from rabbit muscle according to a published method (25).…”
Section: Methodsmentioning
confidence: 99%